Education Management in a Period of Change – Basic Principles and Concepts - Želvys, Rimantas (Acta Paedagogica Vilnensia, 1999)
The article deals with some basic concepts of managing educational change. Different outlooks towards education management are reviewed, theories of education management are discussed, and differing concepts of management and administration are compared. Strategies of educational change are presented and essential managerial traits, necessary for implementing change, are considered. The article also touches upon educational reforms in England and Scandinavia, Central and Eastern Europe. Finally, major problems of Lithuanian educational reform are discussed.